Spatial and temporal patterns in the population and the feeding of Palaemon peringueyi (MacPherson 1990) (Decapoda, Palaemonidae) in the Kariega estuary, South Africa - Nyalungu, Nonhlanhla Precotia Dudu (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
The spatial and temporal patterns in the population demographs and feeding ecology of the caridean shrimp, Palaemon peringueyi, was investigated over a 12 month period in the permanently open Kariega Estuary situated on the south-east coastline of South Africa. Shrimps were sampled monthly from three stations corresponding to the lower, middle and upper reaches of the Kariega Estuary. The shrimps were collected at the different stations using a pull net. Temperature, salinity, dissolved oxygen and % cover of submerged vegetation were measured at each sampling station. Finally, the feeding ecology of the shrimp was investigated employing stable carbon (Î´Â¹Â³C) and nitrogen (Î´Â¹â µN) isotopes analysis. Temperature, salinity, dissolved oxygen and vegetation cover showed distinct seasonal patterns. The shrimps attained total abundances and biomass of between 0 and 245.6 individuals per mÂ² (ind.mâ »Â²) and between 0 and 13.6 grams wet weight per mÂ² (g wwt.mâ »Â²), respectively. Mean abundance ranged between 2.3 (Â± 3.0) and 88 (Â± 27.3) ind.mâ »Â² in the lower reach, between 0.9 (Â± 0.4) to 21.5 (Â± 4.5) ind.mâ »Â² in the middle reach and 0 to 1.6 (Â± 0.5) ind.mâ »Â² in the upper reach. Mean biomass ranged between 0.4 (Â± 0.5) and 4.4 (Â± 1.4) g wwt.mâ »Â² in the lower reach, between 0.1 (Â± 0) to 4.3 (Â± 0.9) g wwt.mâ »Â² in the middle reach and between 0 to 1.6 (Â± 0.5) g wwt.mâ »Â² in the upper reach. Greatest abundances and biomasses were recorded in winter following heavy rainfall within the catchment area. Freshwater inflow which is due to rainfall is thought to provide a cue for the recruitment of marine breeding organisms. The spatial patterns in the distribution of the shrimps showed that juveniles occupied the lower and middle reaches and adults the entire length of the estuary. There were no significant relationships between the abundance and biomass of the shrimps and the selected physico-chemical variables (p > 0.05 in all cases). Results of the stable isotope study indicated that the mean Î´Â¹Â³C of the shrimps in the lower, middle and upper reaches were -12.4 (Â± 1.3) "°, -15.6 (Â± 0.5) "° and -17.5 (Â± 0.5) "°, respectively. The Î´Â¹â µN isotopes of the shrimps in the lower reach was 11.6 (Â± 0.5) "° with middle and upper reaches having similar Î´Â¹â µN values, 13.5 (Â± 0.4) "° and 13.4 (Â± 0.4) "°, respectively. There was no significant difference in the Î´Â¹Â³C and Î´Â¹â µN isotope (p > 0.05) between the sexes of the shrimps. Two-way ANOVA indicated a significant difference in the Î´Â¹Â³C isotope of the shrimps between the sites (p < 0.05). The difference in the Î´Â¹Â³C and Î´Â¹â µN ratios of the shrimps suggests spatial variability in the diet of P. peringueyi within the Kariega Estuary. The diet of the shrimps in the lower reach is primarily composed of Nanozostera capensis epibionts. In the middle reach the diet of the shrimps is likely comprised of the detritus of benthic algae. In the upper reach of the estuary, P. peringueyi likely derives its carbon from a combination of epibionts, benthic algae and detritus derived from Codium.
Keywords: Palaemonidae -- Food -- South Africa; Palaemonidae -- Behavior -- South Africa; Palaemonidae -- Habitat -- South Africa; Estuarine biology -- South Africa; Shrimp populations -- South Africa; Shrimps -- South Africa; Decapoda (Crustacea) -- South Africa